Prediction of mortality in premature neonates. An updated systematic review - Ruth del Río; Marta Thió; Mattia Bosio; Josep Figueras; Martín Iriondo (Anales de Pediatría (English Edition), 2020)
Introduction: Extreme prematurity is associated with high mortality rates. The probability of death at different points in time is a priority for professionals and parents, and needs to be established on an individual basis. The aim of this study is to carry out a systematic review of predictive models of mortality in premature infants that have been published recently. Methods: A double search was performed for article published in PubMed on models predicting mortality in premature neonates. The population studied were premature neonates with a gestational age of ≤30 weeks and/or a weight at birth of ≤1500 g. Works published with new models from June 2010 to July 2019 after a systematic review by Medlock (2011) were included. An assessment was made of the population, characteristics of the model, variables used, measurements of functioning, and validation. Results: Of the 7744 references (1st search) and 1435 (2nd search) found, 31 works were selected, with 8 new models finally being included. Five models (62.5%) were developed in North America and 2 (25%) in Europe. A sequential model (Ambalavanan) enables predictions of mortality to be made at birth, 7, 28 days of life, and 36 weeks post-menstrual. A multiple logistic regression analysis was performed on 87.5% of the models. The population discrimination was measured using odds ratio (75%) and the area under the curve (50%). “internal validation” had been carried out on 5 models. Three models can be accessed on-line. There are no predictive models validated in Spain. Conclusions: The making of decisions based on predictive models can lead to the care given to the premature infant being more individualised and with a better use of resources. Predictive models of mortality in premature neonates in Spain need to be developed. Resumen: Introducción: La prematuridad extrema se asocia a altas tasas de mortalidad. Para profesionales y familias, es prioritario establecer de forma individualizada las probabilidades de muerte en diferentes momentos. El objetivo de este estudio es efectuar una revisión sistemática de modelos predictivos de mortalidad en prematuros publicados recientemente. Métodos: Doble búsqueda de artículos publicados en PubMed sobre modelos predictivos de muerte en prematuros. Población estudiada: prematuros con edad gestacional ≤30 semanas o peso al nacer ≤1.500 g. Inclusión: trabajos publicados con nuevos modelos desde junio del 2010 hasta julio del 2019, tras revisión sistemática de Medlock (2011). Se valoran: población, características de modelos, variables utilizadas, medidas de funcionamiento y validación. Resultados: De 7.744 referencias (primera búsqueda) y 1.435 (segunda búsqueda), se seleccionaron 31 trabajos, incluyéndose al final 8 nuevos modelos. Cinco modelos (62,5%) se desarrollaron en América del Norte y 2 (25%) en Europa. Un modelo secuencial (Ambalavanan) permite realizar predicciones de muerte al nacer, 7, 28 días de vida y 36 semanas posmenstruales. Análisis de regresión logística múltiple en el 87,5% de modelos. La discriminación poblacional se midió por odds ratio (75%) y área bajo la curva (50%). La «validación» se ha realizado en 5 modelos (interna). Tres modelos disponen de acceso online. No hay modelos predictivos validados en España. Conclusiones: La toma de decisiones basada en modelos predictivos permite una mayor individualización de la atención dada a un niño prematuro y una mejor utilización de recursos. Es necesario desarrollar modelos de predicción de mortalidad en prematuros de España.